2019
DOI: 10.3390/foods8100483
|View full text |Cite
|
Sign up to set email alerts
|

Milk Emulsions: Structure and Stability

Abstract: The main aim of this research is to investigate the characteristics of milk and milk proteins as natural emulsifiers. It is still largely unclear how the two main fractions of the milk proteins behave as emulsifier in highly concentrated emulsions. The surface-active effect of these is determined experimentally for emulsions with a high oil content (φ > 0.7), in this case fully refined rapeseed oil. Recent publications have not yet sufficiently investigated how proteins from native milk behave in emulsions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…In addition, SBO droplets in CA-SBO presented a somewhat smaller average size and a narrower span than those in WP-SBO. All of these were in agreement with the established common knowledge that CA demonstrates a stronger emulsifying capacity than WP ( Braun, Hanewald, & Vilgis, 2019 ). Apparently, as did in the pure CA system, CA micelles were observed in the CA-SBO system.…”
Section: Resultssupporting
confidence: 91%
“…In addition, SBO droplets in CA-SBO presented a somewhat smaller average size and a narrower span than those in WP-SBO. All of these were in agreement with the established common knowledge that CA demonstrates a stronger emulsifying capacity than WP ( Braun, Hanewald, & Vilgis, 2019 ). Apparently, as did in the pure CA system, CA micelles were observed in the CA-SBO system.…”
Section: Resultssupporting
confidence: 91%
“…Milk and milk proteins (caseins by around 80% and whey proteins by approximately 20%) are widely used as a natural emulsifier with high oil content. A stabilization of the fat phase in milk can be achieved via different mechanisms of emulsification (Braun et al, 2019). In this research, it can be clearly observed that the pre-heating combined with PEF exposure in raw milk results in significant decrease (p < 0.05) of emulsion stability of raw milk (Table 3).…”
Section: Emulsion Stabilitymentioning
confidence: 64%
“…Regarding the emulsion stability, it was affected by the presence of oil phase. The increasing concentration of oil phase in the milk would results in the unstable emulsions (Braun et al, 2019). Moreover, the measurement of viscosity in milk would give an impact on rheological properties of milk, while the lightness would cause an enzymatic change affecting the milk color, which eventually affect the consumers' preference.…”
Section: Introductionmentioning
confidence: 99%
“…Namun, stabilitas emulsi susu segar maupun susu pasteurisasi non homogenisasi relatif tidak stabil sehingga mengakibatkan terjadinya pemisahan fraksi lemak dan protein pada susu. Beberapa cara yang dapat dilakukan untuk meningkatkan stabilitas emulsi pada susu pasteurisasi yaitu melalui proses homogenisasi maupun penambahan emulsifier (Braun, et al, 2019;Wang, et al, 2016).…”
Section: Respon Optimasi Proses Pasteurisasi Susuunclassified